Housing wealth, social structures and changing narratives. Issue 1 (2nd January 2021) - Forrest, Ray
ABSTRACT: The mid to late twentieth century saw dramatic changes in housing tenure structures. In particular, levels of individual home ownership rose as did the scale and scope of urban residential wealth. This accumulation of housing wealth in these early home ownership societies (e.g. UK, USA, Japan) generated considerable research and policy interest. It was anticipated that social relations and social structures would be transformed by this new and pervasive form of personal wealth. As the process of housing wealth accumulation unfolded, however, new factors and policy imperatives emerged associated with demographic ageing, housing wealth divides, asset-based welfare and ideas of neoliberal self-reliance. From the vantage point of the early twenty-first century, how should we now understand the impact of these developments in relation to housing opportunities, social inequalities and urban change? The implicit promise of housing wealth- for- all through an ever-expanding home ownership has become considerably qualified and severely compromised by financial crises, shifting demographics and structural changes in financialised, neoliberal capitalism. This paper explores the changing narratives around housing wealth among those societies which were the first to develop modern, home ownership institutions and markets. The paper is primarily about how the growth of housing wealth has been perceived and theorized at different periods in those older home ownership systems and the relationship between the changing narrative and the changing socio-economic circumstances around home ownership. The paper concludes with a consideration of the relevance of these experiences for other societies such as Mainland China which has seen more recent and dramatic increases in the level of private property ownership.